Investigating the relationship between cover crop species diversity, composition and function of the soil microbiome - Seitz, Valerie, author; Prenni, Jessica, advisor; Wrighton, Kelly, committee member; Schipanski, Meagan, committee member; Nishimura, Marc, committee member (Colorado State University. Libraries, 2023)
Cropping diversification, such as cover cropping, can contribute to sustainable agriculture by enhancing soil health and promoting ecosystem services through interactions with the soil microbial community. One important mechanism through which cover crops impact soil health is via root exudation, the release of organic compounds from plant roots into the soil region surrounding the roots, the rhizosphere. Root exudation varies among cover crop species, growth stages, and edaphic and environmental conditions resulting in a myriad of effects on the rhizosphere. Plant-derived inputs, like root exudates, modulate the soil microbial community, influencing microbial biomass, community structure, and catalyzing biogeochemistry. As a result, cover crops are linked to microbial changes that impact soil nutrient cycling and organic matter decomposition leading to a legacy impact on primary crop yield and health. Understanding the intricate relationship between cover crop root exudation composition and the soil microbiome is crucial for optimizing cover crop selection, management practices, and harnessing cover crops for precision microbiome management in agroecosystems. My dissertation demonstrates that cover crop root exudation differs considerably across cover crop species, and cultivars within species, and reveals cover crop metabolic impacts on soil microbial composition and function, which play a large role in the generation and maintenance of healthy soils to support our agricultural needs.
Zip file contains appendices A, B, and C.
Keywords: cover crops; metagenomics; root exudates; metabolomics; 16S amplicon; molecular networking